THE IMPLEMENTING OF THE SCHOOL PRINCIPAL TO IMPROVING THE PERFORMANCE OF TEACHERS - Tien Rafida Rafida; Nurika Khalila Daulay; Atika Hanan Julia Harahap (Universitas Islam Negeri (UIN) Sumatera Utara, 2019)
This research is a phenomenologicalin qualitative approach. The data collection methods usingthe observation,interview and documentation. In anal yzing the data the researcher used qualitativeanal ysis with steps of data exposure, data reduction and conclusion drawing. Theresults of his research founded that the function of the school principal incommunicating the vision and mission and goals of the school at SDIT Bina InsanBatang Kuis has been well implemented and the performance of teachers at SDITBina Insan Batang Kuis has not been implemented well enough and the form ofschool principal communication in improving teacher performance at SDIT BinaInsan Batang has not optimally.